Instrumental perforations of the oesophagus and their management. - Moghissi, K (1988)
The records of 39 patients who had developed a perforation of the oesophagus after instrumentation were reviewed. Ten (group A) had cervical and 29 (group B) thoracic oesophageal perforation. Twenty three perforations occurred during dilatation of an oesophageal stricture, 10 during oesophagoscopic removal of a foreign body, and six during diagnostic oesophagoscopy. Of the 21 patients treated within 36 hours (early treatment group), four (19%) died; of the 18 treated more than 36 hours after the perforation (late treatment group), nine (50%) died. None of the 10 patients in group A had strictures and only two presented late. After drainage of the neck and mediastinum the outcome was successful in all patients. Thirteen of the 29 in group B were treated early and four of these died; nine of the 16 treated late died, the total mortality for thoracic perforation being 48%. An oesophageal stricture was present in 23 patients. Twelve of these underwent various forms of conservative surgery and there were 10 deaths. This contrasts with the 11 who received radical treatment with resection and reconstruction, only two of whom died. The six patients with no pre-existing stricture were treated with conservative forms of surgery, with one death.